2011
DOI: 10.3750/aip2011.41.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits of European Hake, <I>Merluccius Merluccius</I> (Actinopterygii: Gadiformes: Merlucciidae), from the Northeastern Mediterranean Sea

Abstract: Background. European hake, Merluccius merluccius, is a major predator in demersal ecosystem, and of great importance for the fishery. Knowledge of the feeding ecology of fish species is essential for implementing a multispecies approach to fishery management. Therefore this work was intended to analyse stomach contents and dietary changes according to fish size, season, sex, and depth to better understanding the ecological role of this species in Adriatic demersal marine communities. Materials and methods.A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
(12 reference statements)
4
21
0
Order By: Relevance
“…When analysing guts content of B. belone, Zorica and Čikeš Keč (2012) found that 94% of prey items were animals, mostly euphasiids and copepods. The kind and size of the prey are usually related to the morphology and the size of the fish (Ross 1978;Stagioni et al 2011). Generally, the jaw size, gut length, reproduction and spreading are related to trophic changes and to intraspecific resource distribution (Ross 1978).…”
Section: Discussionmentioning
confidence: 99%
“…When analysing guts content of B. belone, Zorica and Čikeš Keč (2012) found that 94% of prey items were animals, mostly euphasiids and copepods. The kind and size of the prey are usually related to the morphology and the size of the fish (Ross 1978;Stagioni et al 2011). Generally, the jaw size, gut length, reproduction and spreading are related to trophic changes and to intraspecific resource distribution (Ross 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen individuals each of the 5 size class for a total of 95 individuals were selected for the metabarcoding and morphological analyses. The five size classes (size class 1 = TL 120–149 mm, size class 2 = TL 150–199 mm, size class 3 = TL 200–249 mm, size class 4 = TL 250–299 mm, size class 5 = TL ≥300 mm) were defined on the basis of previous results, keeping in mind size distribution by bathymetric and geographical strata, abundance and feeding habits (Stagioni et al., ). The stomachs were dissected and preserved in 95% ethanol at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although the feeding habits of European hake have been described widely in the Mediterranean (Bozzano, Sardà, & Ríos, 2005;Carpentieri, Colloca, & Ardizzone, 2008;Carpentieri et al, 2005;Cartes, Rey, Lloris, & De Sola, 2004;Froglia, 1973;Papaconstantinou & Caragitsou, 1987;Sartor, Carlini, & De Ranieri, 2003;Stagioni, Montanini, & Vallisneri, 2011;Ungaro, Mannini, & Vrgoč, 2003), they show important differences justified by the opportunistic behavior of this predator. According to these works based on the morphological identification of prey remains in stomachs, adult hakes feed mainly on fish (anchovies, pilchard and gadoid species) and squids whereas the juveniles (<160 mm) feed mainly on crustaceans (preferentially euphausiids and amphipods) in the Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hake diet shifts from euphauiids (Euphausia couchii, Euphausia krohnii) and decapods (Processa sp., Philoderas sp., Solenocea membranacea), consumed by the smaller hakes, to teleost fish (Engraulis encrasicolus, Cepola macrophthalma, Gaidropsarus biscayensis) consumed by larger hakes (Ungaro et al 1993;Carpentieri et al 2005;Stagioni et al 2011). Usually, prey kind and size are related to the morphology and the size of the fish (Ross 1978;Stagioni et al 2011).…”
Section: Discussionmentioning
confidence: 99%